Lithosphere dynamics and sedimentary basins of the Arabian Plate and surrounding areas - Roure, François; Amin, Ammar; Khomsi, Sami; Al Garni, Mansour (Springer, 2017)
This book focuses on the links between deep earth (mantle) and shallow processes in areas of active tectonics in the Arabian Plate and Surrounding Areas. It also provides key information for energy resources in these areas. The book is a compilation of selected papers from the Task Force of the International Lithosphere Program (ILP). It comprises a set of research studies from the Middle East, North Africa and the Mediterranean domain focusing on (1) the architecture, geodynamic evolution and modelling of the Red Sea rift system and its surroundings, and tectonics and sedimentation in the Gulf of Corinth, (2) the crustal architecture and georesources of the North Algerian Offshore, (3) Reservoirs, aquifers and fluid transfers in Saudi Basins, Petroleum systems and salt tectonics in Yemen and (4) Cretaceous-Eocene foreland inversions in Saudi Arabia.
Keywords: Sedimentary basins -- Saudi Arabia.; Lithosphere.; Saudi Arabia.; elektronické knihy; electronic books